Nonlinear relationships between the participation index and key financial assets: A quantile regression analysis - Simsek, Ahmed Ihsan; Bulut, Emre (My University, 2024)
The Participation Index is essential for assessing market sentiment, investor confidence, and financial market direction. Gold, known for its historical role in protecting wealth and providing a stable asset during economic instability, plays a key role in investment portfolios as an alternative guarantee against financial market fluctuations. The USD and EUR are key current currencies in global economics, affecting international trade, financial transactions, and investment decisions. The purpose of this study is to analyze the complex relationships between the Participation Index (KAT) and three significant financial assets: gold, the US dollar (USD), and the Euro (EUR) using Quantile Regression analysis. Daily data between 16.11.2021-08.08.2023 were used in this study. According to the results; the impact of the euro exchange rate on the \"KAT\" variable exhibits a positive relationship, which increases as the quantile level rises. The impact of the exchange rate of the United States Dollar (USD) on the variable defined as \"KAT\" indicates a positive relationship, which intensifies as the quantile level rises. The relationship between gold prices and the \"KAT\" variable shows a positive strengthening impact as the quantile level increases, and these effects demonstrate a high level of statistical significance.
Keywords: BIST; Exchange Rate; Gold; Quantile Regression; Participation Index